Pre-capillary, combined, and post-capillary pulmonary hypertension: a pathophysiological continuum - Opitz, Christian F.; Grünig, Ekkehard (Journal of the American College of Cardiology, 2016)
Background Pulmonary hypertension (PH) is hemodynamically classified as pre-capillary (as seen in idiopathic pulmonary arterial hypertension [IPAH]) or post-capillary (as seen in heart failure with preserved ejection fraction [HFpEF]). Overlaps between these conditions exist. Some patients present with risk factors for left heart disease but pre-capillary PH, whereas patients with HFpEF may have combined pre- and post-capillary PH. Objectives This study sought to further characterize similarities and differences among patient populations with either PH-HFpEF or IPAH. Methods We used registry data to analyze clinical characteristics, hemodynamics, and treatment responses in patients with typical IPAH (<3 risk factors for left heart disease; n = 421), atypical IPAH (≥3 risk factors for left heart disease; n = 139), and PH-HFpEF (n = 226) receiving PH-targeted therapy. Results Compared with typical IPAH, patients with atypical IPAH and PH-HFpEF were older, had a higher body mass index, had more comorbidities, and had a lower 6-min walking distance, whereas mean pulmonary artery pressure (46.9 ± 13.3 mm Hg vs. 43.9 ± 10.7 mm Hg vs. 45.7 ± 9.4 mm Hg, respectively) and cardiac index (2.3 ± 0.8 l/min/m2 vs. 2.2 ± 0.8 l/min/m2 vs. 2.2 ± 0.7 l/min/m2, respectively) were comparable among groups. After initiation of targeted PH therapies, all groups showed improvement in exercise capacity, functional class, and natriuretic peptides from baseline to 12 months, but treatment effects were less pronounced in patients with PH-HFpEF than typical IPAH; with atypical IPAH in between. Survival rates at 1, 3, and 5 years were almost identical for the 3 groups. Conclusions Patients with atypical IPAH share features of both typical IPAH and PH-HFpEF, suggesting that there may be a continuum between these conditions.